Four French sheath-based transradial cerebral angiographies in the elderly: A single neurointerventionalist's experience. Issue 3 (June 2023) - Choi, Dae Han; Yoo, Chan Jong; Park, Cheol Wan; Kim, Myeong Jin
Background: Catheter angiography via transradial access (TRA) is better at reducing access site complications and morbidity than via transfemoral access (TFA). The rate of periprocedural complications increases in elderly populations and using a smaller sheath can help reduce access site complications. The aim of this study was to assess the feasibility and safety of 4 F sheath-based TRA cerebral angiography in elderly patients (≥65 years) and compare it to TFA cerebral angiography. Methods: The medical records of elderly patients undergoing diagnostic cerebral angiography with a single neurointerventionalist via TRA (57 cases, from July 2019 to December 2020) versus TFA (69 cases, from January 2018 to June 2019) were retrospectively reviewed. All TRA angiographies were performed via right radial artery access with a 4 F sheath and a 4 F Simmons 2 catheter. Results: There were no significant differences (TRA vs. TFA) in age (71.1 ± 4.0 vs. 72.1 ± 4.6 years, p = 0.189), accessed vessels (3.9 ± 0.5 vs. 3.9 ± 0.6, p = 0.852), fluoroscopy time (7.1 ± 3.3 vs. 7.6 ± 3.5 min, p = 0.068), and radiation exposure (42.1 ± 15.8 vs. 47.0 ± 13.7 Gy-cm 2, p = 0.067). However, the procedure duration was significantly shorter in the TRA group (17.2 ± 3.9 vs. 19.0 ± 6.0 min, p = 0.003). Painful groin hematoma occurred in 2 of the 69 cases (2.9%) in the TFA group. In the TRA group, access site complications were not occurred; however, catheter kinks occurred in 2 of 57 cases (3.5%). Conclusions: The 4 F sheath-based TRA is a feasible option for diagnostic cerebral angiography in elderly patients. However, care should be taken during catheter manipulation.